Antihypertensive Effects of Esaxerenone in Older Patients with Primary Aldosteronism. (17th January 2023) - Fujimoto, Masanori; Watanabe, Suzuka; Igarashi, Katsushi; Ruike, Yutaro; Ishiwata, Kazuki; Naito, Kumiko; Ishida, Akiko; Koshizaka, Masaya; Suzuki, Sawako; Shiko, Yuki; Koide, Hisashi; Yokote, Koutaro
Abstract : Context . Esaxerenone is a new mineralocorticoid receptor antagonist (MRA). It is an oral nonsteroidal MRA with high MR-binding specificity and antihypertensive effects in patients with essential hypertension and primary aldosteronism (PA). This study aimed to investigate the underlying characteristics of PA patients who responded best to an esaxerenone treatment. Design . Retrospective cohort study. Patients . The data was obtained from a total of 87 PA patients treated with esaxerenone. The treatment group comprised 33 patients who received esaxerenone as first-line therapy and 54 patients that switched from another MRA to esaxerenone. Measurements . Blood pressure (BP), plasma aldosterone concentration (PAC), plasma renin activity (PRA), serum potassium level, estimated glomerular filtration rate (eGFR), urinary albumin-creatinine ratio (UACR), and brain natriuretic peptide (BNP) were assessed before and after treatment with esaxerenone. Patients with overall reductions in their systolic or diastolic BP by 10 mmHg, or more, were considered responders. Unpaired t -tests of the biochemical and personal parameters between responders and nonresponders were run to find the most influencing characteristic for treatment success. Results . BP overall decreased after treatment with esaxerenone (systolic BP: P = 0.025, diastolic BP: P = 0.096 ). Serum potassium levels increased, while eGFR decreased (P = 0.047 and 0.043, respectively). No patients needed a dose reduction or treatment discontinuation of esaxerenone based on the serum potassium and eGFR criteria. UACR and BNP decreased insignificantly. The responders were significantly older than the nonresponders of the esaxerenone treatment (P = 0.0035 ). Conclusions . Esaxerenone was effective in older patients with primary aldosteronism.